2019
DOI: 10.1001/jamaneurol.2019.0617
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Stroke With Rivaroxaban Compared With Aspirin According to Predictors of Atrial Fibrillation

Abstract: IMPORTANCE The NAVIGATE ESUS randomized clinical trial found that 15 mg of rivaroxaban per day does not reduce stroke compared with aspirin in patients with embolic stroke of undetermined source (ESUS); however, it substantially reduces stroke risk in patients with atrial fibrillation (AF).OBJECTIVE To analyze whether rivaroxaban is associated with a reduction of recurrent stroke among patients with ESUS who have an increased risk of AF. DESIGN, SETTING, AND PARTICIPANTS Participants were stratified by predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
101
0
13

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 179 publications
(119 citation statements)
references
References 33 publications
5
101
0
13
Order By: Relevance
“…Historically, the most commonly used measurement of LA size is the linear anterioposterior dimension due to its ease of use. Exploratory subgroup analyses of NAVIGATE ESUS found that rivaroxaban reduced the risk of ischemic stroke in patients with LAD >4.6 cm, and LAD was associated with higher risk of AF [8], but not recurrent stroke [9]. Recent trials such as the ARCADIA trial investigates the use of anticoagulation in ESUS patients at high risk of atrial cardiopathy, adopting a LADi cutoff of ≥3 cm/m 2 as a marker of left atrial enlargement [10].…”
Section: Discussionmentioning
confidence: 99%
“…Historically, the most commonly used measurement of LA size is the linear anterioposterior dimension due to its ease of use. Exploratory subgroup analyses of NAVIGATE ESUS found that rivaroxaban reduced the risk of ischemic stroke in patients with LAD >4.6 cm, and LAD was associated with higher risk of AF [8], but not recurrent stroke [9]. Recent trials such as the ARCADIA trial investigates the use of anticoagulation in ESUS patients at high risk of atrial cardiopathy, adopting a LADi cutoff of ≥3 cm/m 2 as a marker of left atrial enlargement [10].…”
Section: Discussionmentioning
confidence: 99%
“…22 In addition, ongoing research aims to assess the optimal antithrombotic treatment in patients with ESUS and atrial cardiopathy. [23][24][25][26] With regard to PFO, although it is now clear that percutaneous closure of PFO reduces the risk of stroke recurrence in patients younger than 60 years of age, there are many other questions still open, like whether percutaneous PFO closure is beneficial in older patients, and whether the echocardiographic characteristics of the PFO (e.g., the size of the shunt and the presence of atrial septal aneurysm) and the clinical characteristics of the patient (e.g., the RoPE score) could identify a subpopulation which may benefit by percutaneous PFO closure beyond current recommendations. 8,9,[27][28][29] Ongoing and future research will hopefully address many of these open questions and facilitate the improvement of outcomes in this population.…”
Section: Thrombosis and Haemostasismentioning
confidence: 99%
“…In der NAVIGATE-ESUS-Studie wurde bei 4022 Teilnehmen der Durchmesser des linken Vorhofs in der Echokardiographie gemessen [16]. Der mittlere Durchmesser betrug 3,8 cm.…”
Section: Einfluss Der Morphologie Des Linken Vorhofs Auf Das Schlaganunclassified